Properties of High Performance Concrete - Fawzi, Nada Mahdi; Mohammed, ZainAbdeen; Adia, Luma Ahamed (Al-Khwarizmi Engineering Journal, 2010)
The research deals with a new type of high-performance concrete with improved physical properties, which was prepared by using metal additives minutes (Metakaolin) and by studing their impact on the properties of mortar and concrete high-performance through destructive and non destructive tests. This type of concrete is used broadly in public buildings and in other structures . The research involved a number of experiments such as finding the activity index of burned at a temperature of 750 º C according to the standard ( ASTM C-311/03), as well as casting models for the cubic mortar mixtures and concrete containers at different rates of metakaolin ranging between (5% - 20%) as an added part to the cement mix to get a high- compressive strength concrete reaching more than (70) N/mm2 in addition to the decrease in porosity. The research includes standying engineering properties such as density and compressive strength and ultrasonic pulse velocity test and dynamic modulus of elasticity and porosity.